Development of Mathematics Learning Design Using AI-Based Deep Learning Approach to Enhance Students’ Digital Literacy - Silwana, Amalia; Aditya Khoirun Nisa', Lita; Widayanti, Evi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
The deep learning approach has become a focus of national education policy to improve education quality in Indonesia and is being implemented in the current curriculum. However, studies developing holistic deep learning instructional designs supported by Artificial Intelligence (AI), particularly to enhance students’ digital literacy in mathematics, remain limited. This study aimed to develop a mathematics learning design using an AI-based deep learning approach to improve students’ digital literacy, specifically in the topic of elements and nets of cube and cuboid for Grade V. The study employed a Research and Development (R&D) method following the ADDIE development model: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 20 fifth-grade elementary school students from an elementary school in Surabaya. The research instruments consisted of an AI-based deep learning mathematics teaching module for the elements and nets of cube and cuboid topic in Grade V, a digital literacy questionnaire, and a student response questionnaire. The result of this study is a mathematics learning design using AI-based deep learning approach in the form of teaching module in the topic of elements and nets of cube and cuboid is successfully constructed. The teaching module was proven to be highly valid (validation score is 3.64), highly practical (practicality score is 3.39), and effective to enhance students’ digital literacy, with scores increasing from 66.70% to 73.98% (a 7.27% gain). The design aligns with core deep learning principles and supports conceptual understanding, meaningful knowledge construction, and active engagement through AI-based tools. This research contributes to the advancement of mathematics education by offering an implementable and pedagogically grounded mathematics learning design, providing a promising mathematics learning design for integrating AI-based deep learning approaches to enhance students’ digital literacy. Abstrak Pendekatan deep learning menjadi fokus kebijakan pendidikan nasional untuk meningkatkan kualitas pendidikan di Indonesia dan mulai diterapkan dalam kurikulum saat ini. Namun, penelitian yang mengembangkan desain pembelajaran deep learning secara holistik dengan dukungan Artificial Intelligence (AI), khususnya untuk meningkatkan literasi digital siswa dalam matematika, masih terbatas. Penelitian ini bertujuan untuk mengembangkan desain pembelajaran matematika dengan pendekatan deep learning berbasis AI sebagai upaya untuk meningkatkan literasi digital siswa, khususnya pada materi unsur-unsur dan jaring-jaring kubus dan balok kelas V. Penelitian ini menggunakan metode penelitian Research and Development (R&D) dengan model pengembangan Analysis, Design, Development, Implementation, dan Evaluation (ADDIE). Subjek penelitian ini yaitu 20 siswa kelas V SD di salah satu SD di Surabaya. Instrumen penelitian yang digunakan yaitu modul ajar matematika dengan pendekatan deep learning berbasis AI pada materi unsur-unsur dan jaring-jaring kubus dan balok untuk kelas V SD, angket literasi digital, dan angket respons siswa. Penelitian ini menghasilkan desain pembelajaran matematika dengan pendekatan deep learning berbasis AI berupa modul ajar materi unsur-unsur dan jaring-jaring kubus dan balok untuk kelas V SD. Modul ajar terbukti sangat valid (skor validasi yaitu  3.64), sangat praktis  (skor kepraktisan yaitu 3.39), dan efektif dalam meningkatkan literasi digital siswa, dari skor 66.70% ke 73.98% (peningkatan sebesar 7.27%). Desain pembelajaran ini sejalan dengan prinsip pendekatan deep learning dan mendukung pemahaman konseptual, konstruksi pengetahuan yang bermakna, serta keterlibatan aktif siswa melalui alat berbasis AI. Penelitian ini berkontribusi terhadap perkembangan pendidikan matematika dengan menghadirkan desain pembelajaran matematika yang dapat diimplementasikan dan memiliki landasan pedagogis yang kuat, serta menyediakan desain pembelajaran matematika yang potensial dalam mengintegrasikan pendekatan deep learning berbasis AI untuk meningkatkan literasi digital siswa.